المرونة الإدارية في مدارس التعليم الأساسي تجاه تطبيق معايير الجودة الخاصة بالمدرسة صديقة الطفولة في سورية ـ دراسة ميدانية في محافظة دمشق - حلاق, محمد; علاء الدين, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدف هذا البحث إلى معرفة درجة المرونة الإدارية في مدارس التعليم الأساسي تجاه تطبيق معايير الجودة الخاصة بالمدرسة صديقة الطفولة في سورية، وشملت عينته إداريي بعض مدارس محافظة دمشق، وأسفرت نتائجها عن وجود تفاوت حول درجة المرونة تجاه تطبيق معايير الجودة من قبل الإداريين تراوحت ما بين عالية ومتوسطة وضعيفة، كما وجدت فروق دالة إحصائياً تُعزى إلى متغيريّ المؤهل التربوي، والخبرة، وذلك لصالح التربويين، وذوي الخبرة ضمن فئة أكثر من عشر سنوات، بينما لم تظهر فروق وفق متغير الجنس. وبناءً على ذلك قَدَّمَ الباحث عدة مقترحات أهمها تفعيل مبدأ اللامركزية في الإدارة بغية جعلها أكثر مرونةً وانفتاحاً، وتفعيل مشاركة المجتمع المحلي بشكل أوسع، والاهتمام بفئة ذوي الاحتياجات الخاصة من الأطفال، والعمل على تجهيز بيئة تعلُّم مناسبة وجاذبة للأطفال، غنية بتقنيات ووسائل تعليم فعالة وممتعة، والتدريب المستمر للإداريين بتكثيف ورشات العمل وخاصة للوافدين الجدد وفق معايير الجودة للمدرسة صديقة الطفولة. The objective of this survey is to observe the degree of administrative flexibility at elementary public schools according to the quality standards of child-friendly schools in Syria. The specimen of the survey represented administrators of schools in the province of Damascus. The results indicated that there the degree of flexibility in the application of quality standards by administration vary from high, to medium, to low degrees, whereas differences attributed to the variables of educational qualification and experience were in favor of education graduates and those with more than ten years of experience. On the other hand there were no differences attributed to the variable of sex. The researcher has suggested several proposals such as to enhance the non-centralized initiate of administration to be more flexible and open-minded, to enhance the local community, to allocate appropriate material potentials, to combine information technology with learning and teaching, to take more care of children with disabilities, and to provide constant training for administrators by duplicate workshops, especially to the newly-arrived according to the quality standards.